KEDUDUKAN DAN KEKUATAN HUKUM KETERANGAN SAKSI DALAM SISTEM PEMBUKTIAN HUKUM ACARA PERDATA INDONESIA - Lubis, Fauziah; Yazid, Habil; Khalidia, Rifdah; Rangkuty, Putri Mayasari; Lubis, Muhammad Irsyad Tamimi; Harahap, Rizki Marito (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
Witness testimony is one of the most important pieces of evidence in the evidentiary system of civil procedure law in Indonesia. In order to be valid and have legal force, witness testimony must be submitted based on what the witness has seen, heard, or experienced himself. De auditu witness testimony, which is obtained from other people’s stories, has no evidentiary value. In practice, the testimony of one witness is not enough, in accordance with the principle of Unus Testis Nullus Testis. In addition, the law distinguishes between witnesses who can recuse themselves absolutely and relatively. Witnesses are also required to provide testimony under oath, and the testimony will be assessed freely by the judge based on logicality, consistency, and relevance to the case. This research uses normative juridical method with statutory and conceptual approaches. The purpose of this study is to provide a comprehensive understanding of the legal position and strength of witness testimony in the effort to prove in civil court, as well as emphasizing the importance of honesty and direct experience in providing testimony.